Radioprotective Effect of Alk(en)yl Thiosulfates Derived from Allium Vegetables against DNA Damage Caused by X-Ray Irradiation in Cultured Cells: Antiradiation Potential of Onions and Garlic - Hye-Sook Chang; Daiji Endoh; Yushi Ishida; Hiroyuki Takahashi; Shuji Ozawa; Masanobu Hayashi; Akira Yabuki; Osamu Yamato (The Scientific World Journal)
To evaluate a radioprotective effect of sodium n-propyl thiosulfate (NPTS) and sodium 2-propenyl thiosulfate (2PTS) derived from onions and garlic, respectively, rat hepatoma H4IIE cells and mouse lymphoma L5178Y cells were preincubated with each of these compounds for 48 hours at 37°C before receiving 10 Gy of X-ray irradiation. Cell damage caused by the irradiation was quantified as comet tail moment, which represents the degree of DNA damage. X-ray-induced DNA damage was significantly decreased in both H4IIE and L5178Y cells by micromolar concentrations of NPTS and 2PTS compared with the control without the compounds. The protective effect was more potent with 2PTS than NPTS. Onions and garlic have antiradiation potential.